Transcriptome-guided engineering of a native niacin transporter in Lactiplantibacillus plantarum unveils metabolic rewiring for NMN biosynthesis - Kong, Linghui; Li, Xinyu; He, Qing; Yao, Qingshou; Ai, Lianzhong; Qin, Jiayang (Frontiers in Microbiology, 2025)
Introductionβ-nicotinamide mononucleotide (NMN), a precursor of NAD+, holds promise as a functional food ingredient for mitigating age-related decline. This study enhanced NMN biosynthesis in probiotic Lactiplantibacillus plantarum.MethodsA putative niacin transporter, lp2514, was identified via molecular docking and validated by CRISPR/Cas9. A dual-copy expression strategy was also employed to increase NMN production. In parallel, RNA-seq was used to analyze genome-wide transcriptional changes associated with enhanced NMN biosynthesis.ResultsOverexpression of lp2514 increased NMN production by 62.3%, and a dual-copy strategy raised NMN titers to 203 μmol L−1-269% increase compared to empty-vector control without NAM and the highest yield reported in lactic acid bacteria. Transcriptomic analysis revealed 598 differentially expressed genes, including upregulated ribosomal proteins (rpsJ, rplE) and NAD+ salvage enzymes (aspA), indicating enhanced translation and precursor flux. Deleting cinA, encoding a metabolic constraint, further boosted NMN levels, confirming transcriptomic predictions.DiscussionThis combined transporter engineering and transcriptome-guided strategy establishes a food-grade L. plantarum platform for efficient NMN production in functional fermented foods.